2022
DOI: 10.1007/s11133-022-09518-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis as Subculture: Subversions of Health and Medical Knowledges in the Orthorexia Recovery Community on Instagram

Abstract: Diagnoses are powerful tools that fulfill various practical and symbolic functions. In this paper, I examine how a contested diagnosis called orthorexia nervosa has been taken up by users on Instagram, where tens of thousands of posts engage with the topic, many of them from individuals who identify with the condition. I put scholarship on medicalization and diagnosis in conversation with literature on subcultures to foreground the subversive work that is enabled through this diagnosis. Drawing on more than 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 55 publications
(55 reference statements)
2
7
0
Order By: Relevance
“…Users in our study also noted the importance of 'shifting identities' during recovery, mirroring the ndings of Ross Arguedas [9] who identi ed that people with ON experience identity-con ict due to exclusion from health-oriented cultures. These ndings have implications for future therapeutic interventions for ON, which may be successful in harnessing social identity resources to support transition to a recovery identity and targeting beliefs about diets and 'health' that are rooted in societal norms.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Users in our study also noted the importance of 'shifting identities' during recovery, mirroring the ndings of Ross Arguedas [9] who identi ed that people with ON experience identity-con ict due to exclusion from health-oriented cultures. These ndings have implications for future therapeutic interventions for ON, which may be successful in harnessing social identity resources to support transition to a recovery identity and targeting beliefs about diets and 'health' that are rooted in societal norms.…”
Section: Discussionsupporting
confidence: 83%
“…Preliminary research in this area suggests that self-re ection is an important rst step in recovery, through which individuals with ON learn to accept their behaviours as disordered and begin their journey of recovery [8]. In an online ethnography, Ross Arguedas [9] found that shifting identities is central to recovery from ON. The changes that individuals experienced during recovery were associated with a sense of marginalisation or exclusion from health-oriented cultures and were left questioning who they are.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary research in this area suggests that self-reflection is an important first step in recovery, through which individuals with ON learn to accept their behaviours as disordered and begin their journey of recovery [ 9 ]. In an online ethnography, Ross Arguedas [ 10 ] found that shifting identities is central to recovery from ON. The changes that individuals experienced during recovery were associated with a sense of marginalisation or exclusion from health-oriented cultures and were left questioning who they are.…”
Section: Introductionmentioning
confidence: 99%